Assessment of renal involvement in patients with systemic lupus erythematosus in a tertiary care hospital - Akilandeswari, S. Hema; Sathishkumar, J. R. S. Vijay Babu (International Journal of Advances in Medicine, 2019)
Background: Renal involvement in SLE is common. Lupus Nephritis is the major cause of mortality in SLE patients. Renal involvement is a severe form of the disease and subsequent management is planned according to the histopathological class of lupus nephritis. Thus, this study was planned to assess the clinical profile and the extent of renal disease in SLE patients. Methods: A prospective observational study was conducted among SLE patients who got admitted in the Department of General Medicine and Nephrology in Thanjavur Medical College Hospital, Thanjavur from July 2012 to October 2013. Fifty SLE patients who had renal symptoms were included in this study. Results: SLE is Common among females. Common renal presentations were haematuria and proteinuria. 42% of the patients had Class IV lupus nephritis, followed by 24%, 16%, 16%, and 2% of Class III, II, Class V and Class I lupus nephritis respectively. No case of class VI lupus nephritis was reported in this study. ANA was positive among 66%, Anti ds DNA was positive in 64% and C3 level was found to be reduced in 50% of patients. Antiphospholipid antibodies were seen in 2% of the patients. Conclusions: Proteinuria, haematuria, a lower serum C3 level and need for aggressive hypertension management were prominently seen with a worse class of lupus nephritis. Patients with active and proliferative forms of lupus nephritis had a severe course of illness and required aggressive management with immunosuppressants.